Mistral i Llorente. Noves aportacions documentals sobre les relacions occitano-valencianes durant la renaixença - Martí i Adell, Cristòfor (Caplletra. Revista Internacional de Filologia, 2015)
Cristòfor Martí i Adell informs us about the relationship between Frederic Mistral and Teodor Llorente within the general context of Occitano-Valencian relations in the Renaissance. He assesses their ideological and literary content and the possible influence on the patriarch of the Valencian Renaissance of the Occitan poet. These evaluations are based on new and decisive documentary evidences.